The Trouble with Diversifying the Faculty - Michaels, Walter Benn (Kultura-Społeczeństwo-Edukacja, 2012)
This article presents the problem of politics of difference realized within the American educational system, with a special emphasis on higher education. This politics is according to the author based on putting in the center of all educational actions the idea of diversity, as well in creating academic institutions. This key idea becomes in the American context a special significance, regarding the fact that the American society is based on ideology that celebrates multiculturalism and diversity as such. This article presents also an important for the contemporary situation in the United States problem of combining cultural and ethnic diversity on the economical category of difference between various classes. Furthermore, it seems to be more significant in the light of the economic crisis in recent years that affected also American education in the same extent.